Place Matters: A Critical Review of Place Inquiry and Spatial Methods in Education Research. Issue 1 (March 2020) - Butler, Alisha; Sinclair, Kristin A.
Place is an inescapable aspect of daily life and is intimately linked to our life experiences. An expanding body of research has investigated how place shapes the "geography of opportunity" as well as students', families', and stakeholders' experiences in and around schools. While researchers have begun to investigate the spatial context of education, the notion of place remains somewhat underconceptualized in education research. This chapter draws on an interdisciplinary review of 60 empirical, education-related studies to understand how researchers have accounted for place, the theoretical and conceptual frames in which they ground their work, and their data collection methods. We find that researchers have used place inquiry and spatial methods to investigate diverse education-related phenomena, such as school choice and teaching and learning. Beyond using place to identify and describe inequalities, we argue that place inquiry and spatial methodologies can strengthen the potential of education research to disrupt systems of power and oppression by also advancing our knowledge of the nature of and potential solutions to educational injustice.